Refractometric Sensing Using High-Order Diffraction Spots From Ordered Vertical Silicon Nanowire Arrays - Iman Khodadad; Navneet Dhindsa; Simarjeet S. Saini (IEEE Photonics Journal, 2016)
We propose to use high-order diffraction spots from 2-D silicon nanowire (NW) arrays for refractive index sensing based on spatial changes in the diffractive spots position. The NW arrays act both as a refractive index sensor and as dispersive elements, eliminating the need for external spectrometers for the measurement of refractive index changes. The setup uses a simple laser diode source and a low-cost camera and results in higher sensitivity to environmental refractive index changes, as compared with previously demonstrated colorimetric sensors. The sensitivity is greater for higher order diffraction spots, as compared with the lower order ones due to a larger dispersion angle change at higher orders. We also demonstrate that the observed diffraction angle and efficiency of the diffractive orders depend on a number of factors, such as excitation wavelength, NW diameters, pitch, and surrounding medium index. The simple solution of using diffraction spot displacements on a 2-D detector array would provide a novel means of sensing refractive index changes in the surrounding medium of NWs without the burden of complicated spectral analysis.